Unfolded risk-return trade-offs and links to Macroeconomic Dynamics - Liu, Xiaochun (Journal of Banking & Finance, 2017)
A general partial risk-return relation is derived based on return decomposition to allowing for the effect of time-varying skewness and kurtosis on the risk-return trade-off. Empirically estimated for 12 international financial markets, the proposed risk-return trade-off is significantly positive even after controlling for time-varying higher moments. Moreover, the stochastic dominance test reveals that modeling time-varying skewness significantly lowers the level of the risk-return trade-off. More importantly, the empirical evidence shows that the risk-return trade-off is countercyclical in the U.S. markets, consistent with the theoretical habit-formation model of Campbell and Cochrane (1999), whereas the risk-return trade-offs in European and emerging markets appear to be procyclical over a 12-month horizon, but countercyclical for a shorter horizon of 3 months. Finally, common macroeconomic variables can significantly explain risk-return trade-off dynamics.